CONSTRUCTING PSYCHOLOGICAL EXPERIENCE THROUGH TRANSITIVITY: MENTAL AND RELATIONAL PROCESSES IN INDONESIAN POP LYRICS (A CASE STUDY OF MANGU BY FOURTWNTY) - Ramadan Adianto Budiman; Rawuh Yuda Yuwana (PT Akselerasi Karya Mandiri, 2026)
This study investigates how psychological experience and subject positioning are constructed through the transitivity system within contemporary Indonesian pop song lyrics. Drawing on Systemic Functional Linguistics (SFL), the analysis examines the distribution and function of mental, relational, and material processes in Mangu by Fourtwnty, a song characterized by introspective and minimalist lyrical expression. Using qualitative clause-level analysis, the study identifies process types, participant roles, and experiential configurations to explore how agency and inner experience are grammatically realized. The findings reveal a dominant pattern of mental and relational processes, while material processes appear minimal and frequently negated or modalized. This distribution positions the lyrical subject primarily as a Senser and Carrier rather than an Actor, foregrounding internal reflection, relational tension, and constrained agency over physical action. The transitivity configuration constructs a linguistic representation of psychological suspension, where experience is internalized and action remains deferred. By extending previous SFL-based studies on Indonesian cultural texts, this research demonstrates how transitivity functions as a grammatical resource for encoding subjectivity and experiential meaning in non-institutional discourse. The study contributes to discourse stylistics and functional linguistic research by highlighting the role of process selection in shaping representations of emotional experience in contemporary popular music.